LYSINE SUPPLEMENTATION IMPROVES NUTRIENTS DIGESTION, GROWTH PERFORMANCE AND LIVER FUNCTION OF FEMALE BLUE FOXES (Alopex lagopus) IN GROWING PHASE - Q. Jiang1.; F. Yang; X. Gao; X. Wu2 (Journal of Animal and Plant Sciences, 2021)
The present study investigated the effects of lysine supplementation in low-protein diets on nutrients digestibility, growth performance and healthy status of growing female blue foxes (Alopex lagopus). Control animals were fed a diet containing normal protein level (32% of dry matter, DM). Animals in the treatment groups were challenged with low-protein diets supplemented with 0.00%, 0.20%, 0.40%, 0.60%, 0.80% and 1.00% lysine, corresponding to 0.87%, 1.07%, 1.27%, 1.47%, 1.67% and 1.87% total lysine of DM, respectively. Results showed that 1.47% lysine supplementation exerted beneficial effects (P < 0.05) on blue foxes, as evidenced by improved digestibility of crude protein (CP) and several amino acids (aspartic acid, glycine, methionine, isoleucine and tyrosine). Similar effect was observed in N retention (P < 0.05) and the growth performance (P < 0.05). Additionally, the 0.87% lysine group exhibited a significant decrease in blood albumin (ALB) as opposed to the other groups (P < 0.01). Collectively, these findings indicate that quality of low-protein diet can be improved by supplemented lysine without influencing health of female blue foxes at the growing phase. The optimum lysine for maximum performance and low N emission of the growing female blue foxes in approximately 1.47% of DM.
Keywords: lysine; low protein diets; female blue foxes; growing phase; growth performance